POLA PENYEBARAN JENIS BURUNG DI KAWASAN HUTAN DESA NAMO KECAMATAN KULAWI KABUPATEN SIGI - Kristianti, Merlica; Labiro, Elhayat; Ihsan, Moh. (Universitas Tadulako, 2017)
Bird is fauna that can be found from low land up to the upland. The widespread has made birds as potencialÂ natural wealth source of Indonesia. Sulawesi is an area which has a large number of endemic species, and the most various one in Wallacea area.Â Besides its role as an ecosystem balance, bird is also an indicator of environmental change. The forest area of Namo village was one of the bird habitats of primary foreSigi District. The objective of the research was to find out the spread pattern of birds species in the forest of Namo village Kulawi subdistrict Sigi District. The method applied was Point Index Of Abundance (IPA-Count). The data Analysis was done by using Morisita Index (I ), the research applied random method by eight spots. The research was conducted on December 2015 up to the month of February 2016, it was locatec in forest area of namo village Kulawi Subdistrict Sigi District. Based on the result of the research it showed that there were 19 species that represented 13 families in populationof 50 individual. Morisita Index (I ) found that there were 9 species of birds with group spread pattern and only 3 species with similar spread pattern, beside that there were 7 species which spread pattern could not be analized because of individual abundance of each species within one individual.Keywords: Distribution, Birds, Forest